Assessing the English Language Needs of Nursing Students: A Systematic Review : English - Fisma (Fakultas Ilmu Sosial dan Humaniora, Universitas Ibrahimy, 2024)
Previous studies that conducted needs analyses on English for nursing students only concentrated on the target needs at a particular university. This study investigated nursing students' English language needs through a systematic review in order to improve methods of teaching and curriculum development. 14 studies published between 2015 and 2024 were reviewed to highlight the critical role of English proficiency in nursing education and professional practice. This review identified some themes, such as the importance of English for academic and career purposes, the need for developing core language skills, a preference for interactive and practical learning methods, and the requirement for support in online learning environments. The findings suggest the necessity of designing English for Specific Purposes (ESP) and English for Nursing Purposes (ENP) courses tailored to the needs of nursing students. To increase professional and healthcare quality, evidence-based recommendations for curriculum developers, educators, and policymakers are nedded to improve the English language training of nursing students.